An Analysis of Deixis Used by an English Teacher at Methodist Junior High School, Banda Aceh - Cut Gebrina Rahmatika; Andri Wardana (English Education Journal: Jurnal Pengembangan Pendidikan dan Pengembangan Pengajaran Bahasa)
The English teacher uses English to deliver the material. This delivery process can cause misunderstandings among students due to their different backgrounds in English comprehension. In this regard, this study wants to find out whether, in the delivery of material in the classroom, the teacher uses the element of deixis in each of her speech during the learning process. This study aims to discover the types and dominant types of deixis used by the English teacher at Methodist Junior High School Banda Aceh. This research uses a qualitative research design to investigate deixis in the utterances of an English teacher at Methodist Junior High School Banda Aceh. To collect the data, the researcher used documentation. The result of this study showed that all types of deixis proposed by Cruse (2000) are found in the English teacher’s utterances in the classroom. There are 265 words that have deixis, including 184-person deixis, 27 spatial deixis, 11 discourse deixis, 39 temporal deixis, and 4 social deixis. It can be said that person deixis is the most frequently used by English teachers at Methodist Junior High School Banda Aceh. Summarily, it is evident that the English teacher at Methodist Junior High School Banda Aceh applied Cruse’s theory to types of deixis.